The influence of achievement goals on collaborative interactions and knowledge convergence. (August 2017) - Mercier, Emma M.
Abstract: Although there is evidence of the influence of achievement goals on individuals' learning, less is known about their influence on collaborative groups. In this study, 45 pairs of college students engaged in a building task. Twenty-three of the pairs were assigned to a learning goal condition and 22 to a performance goal condition. Pre- and post-test measures were used to quantify differences in outcomes, knowledge convergence and knowledge convergence mechanisms between conditions; qualitative coding was conducted to understand differences in interactions. Results indicated no difference in overall measures of learning and performance outcomes between conditions. However, groups with a learning goal showed more knowledge convergence than groups with a performance goal. Groups with a learning goal engaged in more reflection and more explanations during the task than groups with a performance goal. These results suggest that achievement goals influence interaction behaviors when students are engaged in collaborative activities. Highlights: Dyads were assigned to either a learning or performance goal condition. There was no difference in learning or performance outcome between conditions. Dyads with a learning goal showed more knowledge convergence than dyads with a performance goal. Dyads with a learning goal had more Shared New Knowledge and more Exchanged Prior Knowledge. Dyads with a learning goal engaged in more reflection and explanation.